Immunisation of ferrets and mice with recombinant SARS-CoV-2 spike protein formulated with Advax-SM adjuvant protects against COVID-19 infection. Issue 40 (24th September 2021) - Li, Lei; Honda-Okubo, Yoshikazu; Huang, Ying; Jang, Hyesun; Carlock, Michael A.; Baldwin, Jeremy; Piplani, Sakshi; Bebin-Blackwell, Anne G.; Forgacs, David; Sakamoto, Kaori; Stella, Alberto; Turville, Stuart; et al.
Highlights: COVAX-19 vaccine comprises SARS-CoV-2 spike protein extracellular domain formulated with Advax-SM adjuvant. COVAX-19 vaccine generated neutralising antibody and a Th-1 dominant T-cell response in mice. In immunised ferrets, COVAX-19 vaccine prevented SARS-CoV-2 virus replication in the lungs and nasal cavity. Abstract: The development of a safe and effective vaccine is a key requirement to overcoming the COVID-19 pandemic. Recombinant proteins represent the most reliable and safe vaccine approach but generally require a suitable adjuvant for robust and durable immunity. We used the SARS-CoV-2 genomic sequence and in silico structural modelling to design a recombinant spike protein vaccine (Covax-19™). A synthetic gene encoding the spike extracellular domain (ECD) was inserted into a baculovirus backbone to express the protein in insect cell cultures. The spike ECD was formulated with Advax-SM adjuvant and first tested for immunogenicity in C57BL/6 and BALB/c mice. Covax-19 vaccine induced high spike protein binding antibody levels that neutralised the original lineage B.1.319 virus from which the vaccine spike protein was derived, as well as the variant B.1.1.7 lineage virus. Covax-19 vaccine also induced a high frequency of spike-specific CD4 + and CD8 + memory T-cells with a dominant Th1 phenotype associated with the ability to kill spike-labelled target cells in vivo . Ferrets immunised with Covax-19 vaccine intramuscularly twice 2 weeks apart made spike receptor binding domain (RBD) IgG and were protected against an intranasal challenge with SARS-CoV-2 virus given two weeks after the last immunisation. Notably, ferrets that received the two higher doses of Covax-19 vaccine had no detectable virus in their lungs or in nasal washes at day 3 post-challenge, suggesting that in addition to lung protection, Covax-19 vaccine may have the potential to reduce virus transmission. This data supports advancement of Covax-19 vaccine into human clinical trials.